Book Review: Jonah Berger, Invisible Influence: The Hidden Forces that Shape Behavior. (December 2017) - Mundi, Hardeep Singh
Jonah Berger, Invisible Influence: The Hidden Forces that Shape Behavior, 2016, London, UK: Simon & Schuster, 264 pp., ₹599. ISBN: 9781471148040